DEFOLIADORES DE ENCINAR EN EL ANDÉVALO OCCIDENTAL DE LA PROVINCIA DE HUELVA. COMPARACIÓN ENTRE DOS SITUACIONES PUNTUALES: EL PERIODO 1985-1988 Y EL AÑO 2000 - Granados, C; Ramírez, D; Sánchez, I; López, G; Vázquez, E (III Congreso Forestal Español, 2001)
The great economic and ecological importance of holm oak (Quercus ilex L.) in Spain makes necessary to study the presence and repercussion of leaf-damaging insects in holm oak forests. The field study has been carried out in “Los Millares”, one property of Andévalo Occidental (southern Spain, Andalusia, Huelva). This zone was chosen for two reasons: the existence of previous data about the presence and evolution of leaf-damaging insects during the period 1985-1988, fruit of the work of F.J. Toimil and collaborators; as well as the certainty that this year the population of this insects was very high. The results showed that Tortrix viridana, Archips xylosteana, Periclista andrei and, on a smaller scale, Catocala nynphagoga y Dryobotodes eremita constitute at the moment the main leaf-damaging insects, representing more than 87% of the leaf-damaging found. This population can cause big damages in the holm oak forests, with important economic and ecological losses
Keywords: Andévalo; Huelva; leaf-damaging Quercus ilex; Tortrix viridana

DETERMINACIÓN DE ROTACIONES ÓPTIMAS EN LA APLICACIÓN DE RESALVEOS DE CONVERSIÓN A MONTE ALTO EN TALLARES DE ENCINA Y DE QUEJIGO EN LA ZONA CENTRAL DE LA PENÍNSULA IBÉRICA. - BRAVO, J A; Sánchez, I; Serrada, R (III Congreso Forestal Español, 2001)
Conversion thinning seems to be a good option for most of the coppicce forests of holm oak and gall oak, where the lack of management is causing severe problems. Intensity and rotation of thinning are the two main parameters to be studied. This paper deals with the second one. Six coppicce forests of holm oak and two for gall oak in the Guadalajara province where selected. Those stands had been thinned in a known date, and have been compared with near control stands, which have not been thinned in the past. Diameter growth after thinning has been studied throught rings count and ring width measurement in both kind of stands. 129 trees of holm oak and 79 trees of gall oak have been studied. The main conclusions are the evidence of a significant growth of diameter in holm oaks that is present 11 years after the thinning, while in gall oak results are not so clear. In gall oak just one site showed a positive answer to thinning, that was present until 17 years after. K.W.:
Keywords: conversion thinning; coppicce forest; gall oak; Growth; Holm oak; rotation

Efecto de las inyecciones de fosfonato potásico en tronco de encina (QUERCUS ILEX SUBSP. BALLOTA) SOBRE EL CRECIMIENTO DE RAMILLAS Y LA FRUCTIFICACIÓN. - CORDÓN, S; BRAVO, V; TAPIAS, R; López, G; Sánchez, I (III Congreso Forestal Español, 2001)
The present communication intends to see the answer of the oaks (Quercus ilex subsp. ballota) treateds using antifungal materials (potassium phosphonate) injections to the trunk. In the first year, has been measured the growth of the buds and the production of acorns of three treated oaks and other three not treated, in one property of the Western Andévalo (Andalusia, Huelva).
Keywords: Andévalo; Huelva; Quercus ilex; trunk injections